Análise do comportamento carga recalque e metodologias de controle na implantação de estacas cravadas - Gomes, Romero César (1986)
The main objectives of this study consist of the discussion of the methods usually employed for the control in situ of the behavior of the driven piles, as well as the presentation of other procedures which will allow safer and more suitable analyses. First, the fundamentals of the Wave Equation Analysis are presented and the main relevant points of its application to the problem of pile driving are analyzed. Next, the technique of pile driving control based on the interpretation of the data of rebounds of the pile and the soil are presented, instead of the traditional analysis of the values of the acquired sets at the end of pile driving. Besides, the suitability of the different criteria used in practice for the interpretation of the load tests are discussed. A combination of methods is proposed including these different procedures and aiming at predicting the behavior and evaluation of the performance of driven piles. These methods are then analyzed and applied to a real situation, of which complete driving data and load tests are available.